Frequency of comedication in patients with dementia: Epidemiology / Prevalence, incidence, and outcomes of MCI and dementia. (7th December 2020) - Wurm, Raphael; Stamm, Tanja; Reichardt, Berthold; Parvizi, Tandis; Silvaieh, Sara; König, Theresa; Cetin, Hakan; Stögmann, Elisabeth
Abstract: Background: Comorbidity, especially cardiovascular disease, is frequent in people with dementia. At the same time, access to healthcare professionals and appropriate treatment might be more difficult to obtain. We used the Austrian prescription claims database to analyse the treatment of common comorbidities in patients with dementia and controls. Methods: Insurance claims data covering 98% of the Austrian population were used. We identified patients treated with one of the four approved antidementives (Rivastigmine, Galantamine, Donepezil, Memantine) in the period of 2005‐16, and extracted age‐ and sex‐matched controls that were not being treated with an antidementive. Total number of medication was recorded and odds ratios (OR) for being prescribed that specific medication were calculated separately for the most common classes. Results: We identified 127896 patients treated with an antidementive and matched them to controls in a 1:1 fashion. The median age was 82.3 (IQR 76.7 ‐ 86.6) and 65% were female. Those treated with an antidementive were prescribed significantly fewer drugs in total, including the antidementive drug, compared to controls (median 8 [IQR 5 ‐ 11] vs 9 [5 ‐ 15], p < 0.001, Table 1). The odds of receiving any of the recorded somatic comedication were significantly lower in patients treated with antidementives, with OR ranging from 0.96 for antidiabetics to 0.5 for antihypertensive and 0.34 for anti inflammatory drugs. Conversely, the odds for treatment with psychiatric drugs were significantly higher in this group, with an OR for antidepressants of 1.8 and 4 for antipsychotic drugs (Figure 1). Conclusion: Patients treated with antidementives are less likely to receive treatment for common somatic comorbidities and more likely to receive treatment for psychiatric comorbidities than age and sex‐matched controls. Since available data overwhelmingly suggests that patients with dementia suffer from more comorbidities than those without, this data can be interpreted as evidence for undertreatment of somatic comorbidities in this patient group. with dementia and controls. Additionally, usage of antipsychotic was very frequent and exceeded previously published numbers, emphasizing the need for integrated care for patients with dementia.